Scaling Index Method (SIM): A Novel Technique for Assessment of Local Topological Properties of Porous and Irregular Structures - Sidorenko, Irina; Monetti, Roberto; Bauer, Jan; Müller, Dirk; Räth, Christoph (IntechOpen, 2011)
None